Una mirada a la protección de los conocimientos tradicionales agrícolas desde el contexto latinoamericano - Acea Valdés, Yeney (2016)
Traditional Knowledge becomes common heritage and experience transmitted from generation to generation. It is also the result of the process of contemporary experimentation on the basis of social, environmental and economic nutrients. In Agriculture, this kind of knowledge is part of the quick and fast solution for the lack of food, deficiency of fertilizers, the excess of agrochemical substances and the bad weather. The native Latin-American communities possess a wide flow the area of the traditional knowledge. There is a special place for knowledge of the agricultural sector. The objective of this essay is to identify a space in the framework of law regulations in Latin America that offer protection to the traditional agricultural knowledge, as well as to analyze the treatment of the topic in the context of existing groups in their own region.